Novel Gallium(III), Germanium(IV), and Hafnium(IV) Folate Complexes and Their Spectroscopic, Thermal Decomposition, Morphological, and Biological Characteristics - Abeer A. El-Habeeb (Bioinorganic Chemistry and Applications)
In this study, we describe novel gallium(III), germanium(IV), and hafnium(IV) folate complexes, including their synthesis and analyses. The synthesized folate complexes were also subject to thermal analysis (TGA) to better examine their thermal degradation and kinetic properties. The folate complexes had high stability and were nonspontaneous. The Coats–Redfern and Horowitz–Metzger equations were used to determine thermodynamic parameters and describe the kinetic properties. These complexes were synthesized through the chemical interactions in neutralized media between the folic acid drug ligand (FAH2) with GaCl3, GeCl4, and HfCl4 metal salts at 1 : 2 (metal : ligand) molar ratio. The conductance measurements have low values due to their nonelectrolytic behavior. The X-ray powder diffraction solid powder pattern revealed a semicrystalline nature. In vitro, we screened the synthesized folate chelates for antibacterial and antifungal activities. The inhibition of four bacterial and two fungi pathogens (E. coli, B. subtilis, P. aeruginosa, S. aureus, A. flavus, and Candida albicans) was improved using a folic acid drug relative to the control drug.